Hubungan Perubahan Penggunaan Lahan dengan Limpasan Air Permukiman: Studi Kasus Kota Bogor - Pontoh, Nia Kurniasih (Journal of Regional and City Planning, 2005)
Bogor  City  is  one  of  cities  function ing   as  counter  magnet  forJakarta,  the capital  city  of  Indonesia .  There  is  a  rapid   land  use  change  in  Bogor  that reduce the capacity to absorp  water and increase the   surface run -off  water. Knowing  that  the  position  City  of  Bogor  is  located  in  center  part  of Ciliwung  riverbasin    and  giving  significant  contribution  to   increasing the rate of flow o f river water. Run-off controlling is very important to decrease the  flood  threat  for  Jakarta  and   to increase  the composit e   of   land  water for  City  of  Bogor  itself.  The  study  uses  shift -share  method  analyzes comparing types and area of land use in different time .  The result of study describe  that  the  change  of  land -use  will  be  influenced  much  by  the condition of environment.Keywords: land-use change, run-off water, flood threat